Transcriptome Time-Course Analysis in the Whole Period of Cotton Fiber Development - Zhang, Juncheng; Mei, Huan; Lu, Hejun; Chen, Rui; Hu, Yan; Zhang, Tianzhen (Frontiers in Plant Science, 2022)
Gossypium hirsutum and Gossypium barbadense are widely cultivated tetraploid cotton around the world, and evolved great differences in fiber yield and quality due to independent domestication process. To reveal the genetic basis of the difference, we integrated 90 samples from ten time points during fiber development period, for investigating the dynamics of gene expression changes associated with fiber in G. hirsutum acc. TM-1 and G. barbadense cv. Hai7124 and acc. 3-79. Globally, 44,484 genes expressed in all three cultivars accounting for 61.14% of total genes. About 61.39% (N = 3,412) of cotton transcription factors (TFs) were involved in fiber development, which consist of 58 cotton TF families. Differential analysis of intra- and interspecies showed that 3 DPA had more expression changes. To discover genes with temporally changed expression profiles during the whole fiber development, 1,850 genes predominantly expressed in G. hirsutum and 1,050 in G. barbadense were identified respectively. Based on weighted gene co-expression network (WGCNA) and time-course analysis, several candidate genes, mainly involved in secondary cell wall (SCW) synthesis and phytohormones, were identified in this study, underlying possibly the transcriptional regulation and molecular mechanisms of fiber quality differences between G. barbadense and G. hirsutum. Quantitative real-time PCR (qRT-PCR) validation of candidate genes was consistent with RNA-seq data. Our study provides strong rationale for analysis of gene function and breeding of high-quality cotton.